2018
DOI: 10.1016/j.applanim.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural assessment of the habituation of feral rangeland goats to an intensive farming system

Abstract: Highlights  Habituation methodologies needed for captured feral goats transitioning to intensive rearing.  Simple technique of increased human-animal interaction was tested.  The human-animal interaction resulted in production performance and behavioural benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
0
12
0
3
Order By: Relevance
“…On the other hand, in our experiment, Acceptance was positively related to a high level of arousal on PC2, probably due to the fact that curious and lively animals are more prone to approach humans and to accept to get in contact with them, and this seems in line with the observation of explorative horses engaging in close contact with humans [ 10 ]. An experimental study conducted by Miller et al [ 24 ] confirmed that goats subjected to high degree of positive human interactions were scored by observers as more “calm/content” compared to goats that received a low degree of interactions, scored as more “agitated/scared”. Goats that were more habituated to humans also obtained scores negatively correlated with the number of agonistic contacts and flight speed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in our experiment, Acceptance was positively related to a high level of arousal on PC2, probably due to the fact that curious and lively animals are more prone to approach humans and to accept to get in contact with them, and this seems in line with the observation of explorative horses engaging in close contact with humans [ 10 ]. An experimental study conducted by Miller et al [ 24 ] confirmed that goats subjected to high degree of positive human interactions were scored by observers as more “calm/content” compared to goats that received a low degree of interactions, scored as more “agitated/scared”. Goats that were more habituated to humans also obtained scores negatively correlated with the number of agonistic contacts and flight speed.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are interesting, but the trial was conducted in an experimental setting, thus, in a situation that was very different from that of the present research and of the above mentioned studies conducted in horses and donkeys [ 10 , 12 ] that were conducted on farms. First, the study conducted by Miller et al [ 24 ] used a free choice profile method for term generation and not the fixed list, and QBA observations were conducted watching video clips and not by direct observations. Furthermore, studies involving QBA generally ground on contrasting expressive qualities where treatments are previously selected for their divergent characteristics (as in Miller et al [ 24 ]), but this may unlikely happen in on-farm studies [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated physiological differences (plasma cortisol, packed cell volume) in sheep genotypes, with some more reactive to land transport than others [ 30 ]. In a non-transport example, Miller et al [ 31 ] demonstrated that QBA scores were different for feral goats exposed to varying levels of human interaction, suggesting that the scores reflected habituation and possibly their ability to adapt to the challenge of confinement. Grandin [ 32 ] found that animals with an excitable temperament may have greater difficulty adapting to a situation, while calmer animals may adapt more easily and become less stressed.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioural dimensions identified in this study concur with key qualitative descriptors for sheep demeanor that were identified in previous studies, such as agitated , distressed , alert and curious [ 13 , 15 , 16 , 34 ]. These dimensions used terms semantically consistent with a valence of ‘mood’ (GPA 1) and ‘arousal’ (GPA2) that have been similarly reported elsewhere [ 13 , 27 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%